Comparison of grip strength between professional occupation soldiers and normal adult civilians - Lee, Hyo Taek; Roh, Hyo Lyun (Edelweiss Applied Science and Technology, 2025)
This study aims to measure and compare the grip strength of soldiers and civilians, emphasizing its significance as an indicator of physical health and operational readiness. A cross-sectional study was conducted with 99 male participants (52 soldiers and 47 civilians) whose grip strength was measured using a Jamar hydraulic hand dynamometer. The results showed that military personnel had significantly higher grip strength (average 50 kg) compared to civilians (average 47 kg), with a robust 3 kg difference. No significant differences were observed across different age groups within the soldiers. The findings suggest that systematic military training positively influences grip strength development, reinforcing the role of structured physical conditioning in enhancing operational readiness. These outcomes advocate for integrating grip strength assessments and training into military fitness programs to improve combat preparedness. Furthermore, the results offer valuable insights for civilian physical training strategies focused on functional strength enhancement.